Entre o estranho e o extraordinário: os grotescos nos Atos Apócrifos de Filipe - Soares, Elizangela Aparecida (2023)
This work focuses on the Apocryphal Acts of Philip, a Christian writing dated between the late 4th and the early 5th centuries, which in some of its narratives combines grotesque, monstrous, fantastic, and mythical elements in a world that vacillates between the real and the dreamlike. It is a little explored source, relegated to the shadows of the Apocryphal Acts of the Apostles classified as the major or the first-generation ones (John, Peter, Andrew, Paul, and Thomas). This research assumes that a text such as Acts of Philip is troublesome for traditional methods, since its “excess of imagination” leaves little room for objectivity. Nonetheless, conceiving the excess of imagination as the very richness of the work, the present study proposes an approximation starting from those same elements that marginalize it. To this end, it takes as an approach what has been constructed as a certain theory of the grotesque in the fields of art and literature. Through the mapping and analysis of four subcategories in the domain of the grotesque observed in the Acts of Philip (monster/monstrous, grotesque body, abject and the uncanny), the study aims to explore the potential of the grotesque as a mode of reading that confers symbolic, religious, and cultural value to elements usually abandoned by conventional methods, assuming them as reading keys laden with meaning. It follows from these considerations the thesis according to which the configurations of the grotesque present in Acts of Phi- lip provide a mechanism for reading it. They make it possible to infer the idealization of a worldview that pervades the narrative, as well as to observe the presentation and defense of models of representation, existence and relationships that converge to this very worldview: ways of perceiving and experiencing otherness, oneself, and reality.(AU)